Large Heterogeneity in Mean Durations of Labor Analgesia Among Hospitals Reporting to the American Society of Anesthesiologists' Anesthesia Quality Institute. Issue 2 (June 2016) - Flood, Pamela; Dexter, Franklin; Ledolter, Johannes; Dutton, Richard P.
Abstract : ( Anesth Analg . 2015;121(5):1283–1289) Expected duration of labor varies widely and depends on multiple covariates, ranging from biological factors, such as genotype, obesity and fetal weight, to obstetrical practices, such as intention to reduce infection risk or provide a more natural birth. Such variability in mean duration of labor analgesia for vaginal delivery may influence appropriate equitable fee-for-service payments. In order to address this issue, the authors of the present study determined mean durations of labor analgesia among hospitals in the United States.